2019
DOI: 10.1002/aic.16557
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the pressure drop across polydisperse packed beds in cake filtration

Abstract: Filtration is the separation of solid–liquid mixtures. In this study, we assess the predictive power of Kozeny–Carman model for systems operated at low Reynolds numbers and relatively high pressure drops. We find substantial agreement between the K‐C model and experiment only for systems that exhibit tight void size distribution. Dramatic disagreement is observed for particle beds that exhibit wide void size distributions. We propose a modified modeling approach, based on a bimodal void distribution, by introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The investigation of porous media has benefited from the DEM simulations of, for example, Reboul et al [25], who focused on the void size distribution of a packed bed, and Dong et al [26], who focused on the influence of different forces on particles while sedimenting and forming filter cakes. More recently, Zhang and McCarthy [27] proposed a modified modeling approach for cake filtration by implementing a DEM-coupled method and comparing it with the classic Kozeny-Carman model [28]. The modified model more accurately predicted the flow rates in the case of polydisperse systems.…”
Section: Romanmentioning
confidence: 99%
“…The investigation of porous media has benefited from the DEM simulations of, for example, Reboul et al [25], who focused on the void size distribution of a packed bed, and Dong et al [26], who focused on the influence of different forces on particles while sedimenting and forming filter cakes. More recently, Zhang and McCarthy [27] proposed a modified modeling approach for cake filtration by implementing a DEM-coupled method and comparing it with the classic Kozeny-Carman model [28]. The modified model more accurately predicted the flow rates in the case of polydisperse systems.…”
Section: Romanmentioning
confidence: 99%
“…the number of particle layers along the channel height is too small to neglect the contribution of the flow near the channel surface. [56][57][58][59] Secondly, because of the heterogeneous microstructure 60,61 of the accumulation with the presence of void zones, 44,57,62 which inevitably favours an heterogeneous flow through the porous structure. We also observed that when we get closer to the CCC, at I = 100 mM, the value of f remains unchanged (Fig.…”
Section: Flow Conditions Inside the Particle Accumulationmentioning
confidence: 99%
“…Finally, we investigate the effectiveness of the Carman-Kozeny (C-K) model for permeability in our system through observations of our system's flow profile. Previous work has identified failures of the C-K model, which include systems of wide void size distribution [34] and non-uniform microstructure [35][36][37]. Further modifications of the C-K model have been suggested in the form of changes to the Kozeny factor [38], and the replacing particle diamter with the hydraulic diameter [37,39].…”
Section: Introductionmentioning
confidence: 99%